Development of an efficient solar concentrator and utilization in copper extraction from copper minerals - Valdivieso, Alejandro; Yang, Ke; Camacho Conzález, Luis Fernando; Santos García, Fátima MI; Molinari, Yuri Nahmad (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
A novel and cost-effective solar concentrator has been developed to enhance efficient copper extraction. Based on the criteria for a stationary compound parabolic concentrator, the reflector geometry incorporates a half-spherical curve and a strength line. This design significantly improves the concentrator’s ability to capture more marginal rays compared to widely used commercial solar concentrators. In this study, a newly configured solar concentrator was constructed with aluminum sheet and tested in San Luis Potosi, Mexico, with a comprehensive performance analysis. The investigation revealed an optical efficiency of 0.73 and a maximum thermal efficiency of 68%. Experimental results demonstrated that the solar collector could absorb solar radiation throughout the year without the need for a tracking system. It efficiently facilitated the copper sulfide ore leaching process at a medium temperature of approximately 70 °C. Capital cost analysis indicated an exceptionally low unit manufacturing cost of only 125 USD /m2. The study further proposes that the implementation of this solar collector could potentially double the copper recovery rate and triple the annual increase in copper cement without contributing to CO2 emissions. Additionally, the feasibility of deploying this new concentrator on an industrial scale was thoroughly evaluated to provide a substantial support for advancing cleaner copper production technology through further innovation.